Pengembangan instrumen penilaian afektif dalam Pendidikan Agama Islam - Baha Shofa Mijdal; Tasman Hamami; Iqbal Ahsanul Aula; Adisti Anggraini; Evi Sulvaningsih (Curricula: Journal of Curriculum Development, 2026)
Affective assessment is essential in Islamic Religious Education because it fosters students’ attitudes, values, religiosity, and Islamic character. This study theoretically analyzes the development of affective assessment instruments, emphasizing their relevance and importance in contemporary education. The study addresses the limited use of systematic, measurable instruments to assess students’ attitudes, values, and character. The method used in this study is library research, examining classical and contemporary literature on affective domain taxonomy, authentic assessment, Islamic educational evaluation, and character education. The findings show that affective assessment instruments can be developed through observation, anecdotal records, reflective journals, attitude questionnaires, and portfolios, with consideration of validity, reliability, objectivity, and alignment with Islamic values such as justice, honesty, and responsibility. The main finding confirms that the development of affective assessment instruments in Islamic Religious Education is not only methodological but also normative because it integrates modern affective taxonomy with Islamic educational principles. This study concludes that affective domain assessment is an essential component of Islamic Religious Education because it connects religious knowledge with the internalization of Islamic values in students’ attitudes and behavior.